Design of Ultra-Wideband (UWB) horn antenna for non-destructive fruit quality monitoring - Siti Fatihah, hazali; Syamimi Mardiah, Shaharum; Ahmad Afif, Mohd Faudzi; Sabira, Khatun; Mohamad Shaiful, Abdul Karim; Nurhafizah, Abu Talip (Springer Singapore, 2018)
This paper presents an ultra-wideband pyramidal horn antenna for non-destructive fruit quality monitoring system. The proposed design simulation operates in the frequency range of 3.1 GHz to 10.6 GHz. The antenna is supported by the rectangular waveguide feeder. The design is chosen based on the ability of the antenna to transmit and receive signal with wide bandwidth, high directivity and gain, and low Voltage Standing Wave Ratio. The antenna is designed and simulated by using Computer Simulation Technology Microwave Studio. The simulation result also validated by the experimental result. The simulation result shows that the proposed UWB pyramidal horn antenna exhibits small return loss with low VSWR as well as good radiation pattern in the frequency range of 3.1- 10.6 GHz.